(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Women’s health is extremely valuable and source of healthy nation. There are so many diseases that affects quality of life of women; cervical erosion is one among them. On the basis of etiopathogenesis, clinical features, complications and principles of treatment; Karnini Yonivyapad is very near to cervical erosion. ’Karnini Yonivyapada’ is a disease caused by vitiation of Vata and Kapha dosha while affected dhatu is Rakta. Treatment is aimed at Vata-Kaphashamaka and Raktashodhaka. In cervical erosion, there is replacement of squamous epithelium of ectocervix by columnar epithelium of endo cervical canal. Although it is a benign condition but ignorance of this disease may lead to infertility and cervical malignancy. The treatment of cervical erosion is designed to destruct the columnar epithelium and to promote the re-epithelization of the squamous tissues. Electric cauterization and laser are the standard treatment modalities of erosion in modern medical science which are the modified form of Agnikarma but so many side effect associated with them. In the present study, the management of cervical erosion was done through Agnikarma by Jamabbadan shalaka and found as better alternative in the management of Karnini (Cervical erosion).